Hazard Identification And Risk Control In The Preparatory Department At PT. Gajah Duduk Pekalongan District - Setiaji, Ari Nuriman; Budiyanto, Slamet; Priharwanti, Ardiana (Universitas Pekalongan, 2024)
The development of industry in Indonesia is currently very rapid. This is also accompanied by the risk of increasing and diverse dangers due to technological experts where the use of increasingly complex machines and work equipment to support the production process causes occupational health and safety problems. The same thing happened at PT. Gajah Duduk Pekalongan. This study focused on the scope of the preparation area, because this section has a great potential for work accidents. This study aims to determine efforts to assess and control hazards and risks at PT. Gajah Duduk. The method used is qualitative research. Data were obtained from the results of in-depth interviews and observations. Research Results: show the importance of the use of personal protective equipment (PPE) and standard operating procedures (SOP) that the company has set. The company needs to emphasize job training institutions to obtain information and work systematically at the training stage for new employees. Conclusion: The production process in the preparation unit has not been running optimally. Several things can still be used as evaluation material for the company related to potential hazards that can endanger workers. Suggestion: Support is expected from various parties, PT. Gajah Duduk to protect every worker and increase company production